Affinity versus specificity in coupled binding and folding reactions. Issue 8 (9th August 2019) - Gianni, Stefano; Jemth, Per
Abstract: Intrinsically disordered protein regions may fold upon binding to an interaction partner. It is often argued that such coupled binding and folding enables the combination of high specificity with low affinity. The basic tenet is that an unfavorable folding equilibrium will make the overall binding weaker while maintaining the interaction interface. While theoretically solid, we argue that this concept may be misleading for intrinsically disordered proteins. In fact, experimental evidence suggests that interactions of disordered regions usually involve extended conformations. In such cases, the disordered region is exceptionally unlikely to fold into a bound conformation in the absence of its binding partner. Instead, these disordered regions can bind to their partners in multiple different conformations and then fold into the native bound complex, thus, if anything, increasing the affinity through folding. We concede that (de)stabilization of native structural elements such as helices will modulate affinity, but this could work both ways, decreasing or increasing the stability of the complex. Moreover, experimental data show that intrinsically disordered binding regions display a range of affinities and specificities dictated by the particular side chains and length of the disordered region and not necessarily by the fact that they are disordered. We find it more likely that intrinsically disordered regions are common in protein–protein interactions because they increase the repertoire of binding partners, providing an accessible route to evolve interactions rather than providing a stability–affinity trade-off.